Efficacy of feed-based monovalent and multivalent vaccines against bacterial diseases in Epinephelus fuscoguttus (Forsskal, 1775) X E. lanceolatus (Bloch, 1790) (grouper) and Lates calcarifer (Bloch, 1790) (seabass) - Mohamad, Mohamad Aslah (2022)
Vibriosis, streptococcosis, and MAS are commonly isolated from disease outbreaks in aquaculture farms in Malaysia. The diseases lead to significant economic loss in the country. It is critical to develop highly effective vaccines against these diseases to avoid antibiotics. However, limitations in vaccine development such as injection vaccination, using adjuvants that may stimulate adverse reactions in the host, and using non-cross protective antigens may slow the vaccine development. Therefore, the objectives of the study were (1) to develop a feed-based palm oil adjuvanted multivalent vaccine containing whole cells of inactivated Vibrio harveyi strain Vh1, Streptococcus agalactiae strain Sa2k, and Aeromonas hydrophila strain Ah1sa5, and a feed-based cross-protective monovalent vaccine containing whole cells of inactivated V. harveyi strain Vh1, (2) to assess the specific immune response and the relative expression of immune-related genes following vaccination with the feed-based vaccines, (3) to evaluate the protective efficacy of the feed-based vaccines following experimental challenges with multiple Vibrio spp. in Asian seabass, Lates calcarifer and (4) to evaluate the field efficacy of the feed-based vaccines against vibriosis in farmed hybrid grouper (Epinephelus fuscoguttus × E. lanceolatus). Briefly, a feed-based multivalent vaccine was developed from formalin-inactivated V. harveyi strain Vh1, S. agalactiae strain Sa2k, and A. hydrophila strain Ah1sa5 incorporated into powdered feed with the addition of palm oil adjuvant. While the monovalent vaccine was developed from formalin-inactivated V. harveyi strain Vh1, incorporated into powdered feed with palm oil adjuvant. A commercial feed pellet (Star Feed, Klang, Malaysia) was used as a negative control. The feed-based vaccines and control feed was later assessed for feed quality and safety analysis. The results revealed that the feed-based vaccines contained good nutritional compositions, even after reformulations. Besides, the vaccinated feed was tested to be safe for fish consumption and showed positive effects on fish growth. Further analysis was done on an immune response study with 450 Asian seabass, Lates calcarifer juveniles (15.8±2.6g), divided equally into three groups with triplicate. Group 1 was fed with multivalent vaccinated feed, Group 2 with V. harveyi monovalent vaccinated feed, and Group 3 with commercial feed. Vaccinations were carried out by feeding the fish with the feed-based vaccine on days 0 and 14 at 5% body weight. Serum and gut samples were collected weekly for IgM antibody, lysozyme activity, and gene expression analysis. A challenged trial was conducted on week 4 post-immunization. The results showed that the specific IgM antibody and non-specific lysozyme activity levels in the serum of the multivalent and monovalent vaccinated groups were more highly stimulated than the control group at most of the sampling period. Besides, the vaccinated fish showed significant upregulation (P < 0.05) of the immune-related genes with the highest immune gene expression in the multivalent vaccinated group was seen in the Dendritic Cells gene at week 6 (11.47- fold), followed by the CCL4 gene (7.79-fold) at week 4. While the highest expression in the monovalent vaccinated group was seen in the MHC-I gene at week 3 (5.23-fold), followed by the C3 gene at week 4 (3.67-fold). Bacterial challenge against V. harveyi, S. agalactiae, and A. hydrophila showed that the multivalent vaccine gave an RPS value of 75±7.07%, 85± 7.07% and 70±0.00% against V. harveyi, S. agalactiae dan A. hydrophila, respectively while 70±0.00% against the combined bacteria, while the monovalent vaccine gave 70±0.00% against V. harveyi infection. Despite the vast potential applications of the multivalent vaccine against multiple bacterial infections, this current study focuses on the efficacy of the feed-based multivalent vaccine against major Vibrio spp in cultured marine fishes in Malaysia, such as V. harveyi, V. alginolyticus, and V. parahaemolyticus. The monovalent V. harveyi vaccine was also tested in this study to determine its cross-protective efficacy against multiple Vibrio spp. and compared with the multivalent vaccine to determine whether the combined vaccines could induce a more robust immune response without antigen competition. This study revealed significantly higher antibody levels (P < 0.05) in the multivalent and monovalent vaccinated fish following the double booster regiment. Post-challenge with specific bacteria at week 10 showed that the IgM antibody levels in serum, body mucus, and gut lavage fluid of the multivalent and monovalent vaccinated group were significantly higher until week 13 than in the control groups. The results were supported by the bacterial challenge study with multiple Vibrio spp. The multivalent vaccine an RPS value of 85±7.07%, 80± 0.00% and 75±7.07% against V. harveyi, V. parahaemolyticus, and V. alginolyticus, respectively while 70±0.00% against the combined bacteria, while the monovalent vaccine gave 75±7.07%, 75±7.07% and 70±0.00% against V. harveyi, V. parahaemolyticus, and V. alginolyticus, respectively and 70±0.00% against the combined Vibrio spp. infection. Finally, a field trial was conducted on a mariculture farm to study the field efficacy of the multivalent and monovalent vaccines under commercial fish farming conditions. The stimulation of the immune system in the multivalent and monovalent vaccinated group was shown by the increase of the IgM levels after immunization as early as week 2, peaked at week 6, and remained significantly high until week 12. The antibody stimulation indicates that the protection might be possible for a period of 12 weeks (3 months). The vaccine groups resulted in a higher survival rate than the control groups, with 79.75 ±0.07% survival in the multivalent vaccine group and 75.25±4.75% survival in the monovalent vaccine group compared to 65.10±0.14% in the control group after a 16-week field trial. Furthermore, better feed conversion efficiency and weight gain were clearly shown in the vaccine groups. Combining the results reveals that the feed-based multivalent and monovalent vaccine effectively induced an immune response against vibriosis, and the multivalent vaccine is potentially effective against streptococcosis and MAS. The monovalent vaccine was found to be as good as the multivalent vaccine against vibriosis, and the combined antigens in the multivalent vaccine do not significantly contribute to higher antibody stimulation and protection against the Vibrio spp than the monovalent vaccine. However, the multivalent vaccine could provide wider protection against other diseases than the monovalent vaccine. Both feed-based vaccines are highly potential for commercialization due to their novelty, industrially applicable, and effectiveness in protecting fish. The vaccine can be marketed and applied to the aquaculture and mariculture industries.